IMPROVEMENT OF INNOVATIVE MECHANISMS OF THE ORGANIZATION OF SOCIAL EDUCATION IN FAMILIES (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article discusses the issues of social education of youth, improvement of innovative mechanisms for organizing social education in modern families in the context of globalization.